A Comparative Analysis of the Anatomical Variability in Pinus brutia Ten. Essential Oils - Jorge M. S. Faria; Ana Margarida Rodrigues; Ana Fundurulic (Environmental Sciences Proceedings, 2021)
Pinus brutia Ten. is distributed throughout the Eastern Mediterranean, mainly in Turkey and bordering countries. Pine essential oils (EOs), mainly comprised of terpenoid volatiles, have high commercial value and a wide range of biological applications as repellents, insecticides, antivirals, antimicrobials and antioxidants. The present work reviewed the chemical variability of EOs reported for P. brutia trees and related bioproducts. The major EO components (≥20%) reported were α-pinene, β-pinene and δ-3-carene, which generally comprised 50–90% of the EO composition. δ-3-Carene showed the highest variability, suggesting the occurrence of chemotypes. Assessing the variability of EOs extracted from different tree parts or tree bioproducts can provide useful information for guided P. brutia EO extraction according to its intended purpose.